(untitled) (Third Sector Social Economic Review, 2020)
The aim of this study is to investigate the firm spesific and macroeconomic factors affecting the profitability of manufacturing firms quated on Borsa İstanbul. The period of 2009-2019, a sample of 129 manufacturing firms operated in Borsa İstanbul are grouped according to their asset size. As a result of the grouping a total of 80 firms, 20 of which are large, 29 are medium sized and 31 are small, have been analyzed. Quarterly data of firms are used in the anaylsis and , regression anaylsis is employed. Return on asset ratio, return on equity ratio and earnings before interest and taxes raito are used as dependent variables; firm size, liquidity, leverage and tangibility are used as firm spesific independent variables and also GDP growth rate and interest rate are used as macroeconomic independent variables. According to the results; the leverage raito and tangibility ratio effect whole profitability ratios negatively while GDP growth rate effects positively.